PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH BERBASIS KOMUNITAS (Studi Kasus Bank Sampah Tri Guyup Rukun, Kabupaten Purworejo) - ., Indrawati (Journal of Politic and Government Studies, 2019)
This study aims to describe community participation in community-based waste management at Tri Guyub Rukun Waste Bank, which includes background participation, forms of participation and level of participation. In addition, to see how the factors that encourage and hinder community participation in waste management. The research method used in this study is a combination of qualitative and quantitative descriptive. The informants of this study were administrators and customers of the waste bank.The results of the study showed that the background of the community participated, namely the socialization of the waste bank management, local village government support, and individual motivation. The form of participation that was carried out included the participation of thought, energy, skills and goods, while participation in the form of money was not found. Community participation in Tri Guyub Rukun Garbage Bank for external matters according to Arstein is at the degree of citizen power level, while for things that are internal at the level of non participation. Factors that encourage the existence of norms (norms), trust (trust) and network (network). The inhibiting factors are infrastructure, time, communication, stakeholders, distance, and unexpected agenda.Suggestions from this study are that Tri Guyub Rukun Waste Bank administrators increase the number of field officers, make neat transportation schedules, make permanent shelter posts and not too far away, improve waste segregation socialization, provide incentives for customers who contribute greatly, provide training in making cycle goods repeat from waste, create smooth communication, and build public opinion related to the planning of waste management programs.Keywords: Community Participation, Waste Management, Community